On The Issue Of Barbaroba Celebration In Svaneti And Shida Kartli - Koshoridze, Tamila (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2017)
One of the celebrations known for Svanetian people is the day of the goddess Barbare (Barboli) who was considered as a rescuer of cows, their fertility and reproduction. In Svanetian beliefs Barbare was the owner of the cows, she could recover or even kill them according to her wish. The annual cycle of folk holidays in Shida Kartli begins with Barbaroba – every family bakes walnut pies . Another traditional meal for Barbaroba is Lobiani - a bean pie. In the past people used to take them in streets and give them to everyone. Svanetian people believed also in “mekvle” which was a person - a first visitor in their homes at Barbare holiday. “Mekvle” was believed as a definer of the future of a host family. December 17 already a Christian holiday commemorating St. Barbare, who is considered as the savior of Children. The name of Barbare comprises both Christian and pagan beliefs, she is the symbol of productivity and fertility in pagan beliefs and the savior of children from diseases in Christian faith.